ANALISIS VARIANS BIAYA OPERASIONAL DALAM MENGUKUR EFEKTIVITAS BIAYA OPERASIONAL (STUDI KASUS PT. PEGADAIAN KANTOR WILAYAH X BANDUNG) - Yati Mulyati; Sherin Hilmi Marsyanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Budgeting is an important planning in running the company's business. PT Pegadaian Kanwil X Bandung, one of the state-owned enterprises engaged in financing services, has made periodic budgets as a guide for the company in carrying out its programs. In line with the running of his business in the last three years, the realization of the budget is not in accordance with the predetermined plan. Therefore, the authors are interested in knowing the procedures for preparing the operational cost budget, the realization of the operational cost budget and the analysis of operational cost variance in measuring the effectiveness of operational costs. This research is a qualitative descriptive study, using literature studies and secondary data on operating budgets for the 2019-202 period. The results of the study provide an illustration that the company has made a budget in accordance with established procedures, the realization of the budget can be evaluated annually and the analysis of variance within a period of three years as a whole provides a favorable benefit.